Exchanges on Obesity and Smoking - Kaebnick, Gregory E. (The Hastings Center report, 2013)
The January-February issue of the Report introduced a number of new features designed to provide opportunities for further give-and-take in our pages. In this issue, we put to use our revamped letters to the editor, Exchange, with a set of commentaries on another of the January-February articles, Daniel Callahan's “Obesity: Chasing an Elusive Epidemic.” Commentaries in Other Voices and special reports are planned and solicited, in consultation with scholars in the field and with the guest editors of the special reports, but our hope is that Exchange will provide an opportunity for unsolicited voices in the Report. Of course, Callahan's controversial article is all too good for drumming up unsolicited commentary: Callahan argued that the rise in obesity requires an aggressive public health campaign that employs some stigmatization of obesity.